2015
DOI: 10.1002/biof.1224
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B induces an Nrf2‐mediated thioredoxin expression and suppresses the activation of inflammasome in vitro and in vivo

Abstract: Reactive oxygen species (ROS)-mediated activation of inflammasome is involved in the development of a wide spectrum of diseases. We aimed to investigate whether (-)schisandrin B [(-)Sch B], a phytochemical that can induce cellular antioxidant response, can suppress the inflammasome activation. Results showed that (-)Sch B can induce an nuclear factor erythroid 2-related factor 2-driven thioredoxin expression in primary peritoneal macrophages and cultured RAW264.7 macrophages. A 4-h priming of peritoneal macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
3
12
1
Order By: Relevance
“…This was corroborated by the observation that co-incubation with a CYP inhibitor (or NAC) as well as Nrf2 knockdown could attenuate the anti-inflammatory action elicited by Sch B. A recent finding in our laboratory has shown that the Sch B-induced expression of TRX can inhibit the activation of NLRP3 inflammasome in cultured mouse macrophages [ 30 ]. Taken together, the anti-inflammatory action of Sch B may, at least in part, be secondary to the induction of an antioxidant response.…”
Section: Discussionmentioning
confidence: 65%
“…This was corroborated by the observation that co-incubation with a CYP inhibitor (or NAC) as well as Nrf2 knockdown could attenuate the anti-inflammatory action elicited by Sch B. A recent finding in our laboratory has shown that the Sch B-induced expression of TRX can inhibit the activation of NLRP3 inflammasome in cultured mouse macrophages [ 30 ]. Taken together, the anti-inflammatory action of Sch B may, at least in part, be secondary to the induction of an antioxidant response.…”
Section: Discussionmentioning
confidence: 65%
“… 46 49 Interestingly, several studies have revealed that Sch B exhibited anti-inflammatory and antioxidant activities by activating Nrf2 pathways. 50 , 51 In addition, recent reports also showed that S. chinensis extract and Sch B could activate Nrf2 reporter gene and induce the expression of HO-1 and NQO1. 52 However, whether Sch B activates Nrf2-ARE signaling against liver fibrosis has not been studied.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, Pei-Yi Tsai demonstrated that epigallocatechin-3-gallate had prophylactic effects on lupus nephritis by increasing the Nrf2 antioxidant signaling pathway and inhibiting renal NLRP3 inflammasome activation (11), which could also be applied to the treatment of glomerulonephritis (50). In addition, schisandrin B was reported to induce Nrf2 expression and attenuate ROSdependent peritonitis (26). Although studies have revealed that enhancing Nrf2 and suppressing NLRP3 can be used to treat inflammation, it is still unknown whether there is a crosslink between the Nrf2-ARE pathway and NLRP3 inflammasome and whether Nrf2 inducers could be adopted to protect against NLRP3-associated diseases.…”
Section: Discussionmentioning
confidence: 99%